Gender, Poverty and Energy Nexus: Unpacking The Conflict in Zimbabwe (International Journal of Sustainable Energy and Environmental Research, 2014)
In year 2000, the Zimbabwean government embarked on a national land reform programme meant to redistribute land between the minority white commercial farmers and the majority black peasant farmers. In the roll-out of the programme, women were considered an important cog though they had no specific quota in the allocation of land. The eventual land ownership structure was that over three hundred thousand black indigenous peasants had suddenly become new and larger land owners, over-crowding the once sparsely populated commercial farming areas. What did not get into the minds of many especially women and the youth was the impending challenge to do with the firewood availability for their energy requirements. Now over ten years into the land reform exercise, the youth are now embroiled in firewood poaching for resale in both the neighbourhood and the nearby urban areas where electricity availability is a nightmare. This massive criminal activity has also negatively affected women who have to bear the exorbitant firewood prices and deforestation, experience land degradation and witness cat-and-mouse wars between the youth and law enforcement agents. This paper examines the gender, poverty and energy nexus in rural areas of Bindura district, Zimbabwe. The study specifically focuses on two administrative wards; 3 and 4 in the Matepatepa commercial farming area of Bindura. It is the submission of the researcher that indeed, women have massively degraded and deforested the once thick forests for self-sustenance and in the process created conflicts amongst themselves.